Therapeutic Leukapheresis in Pediatric Leukemia: Utilization Trend and Early Outcomes in a US Nationwide Cohort. Issue 2 (March 2022) - Takahashi, Takuto; Turcotte, Lucie M.; Gordon, Peter M.; Johnson, Andrew D.; Rubin, Nathan; Spector, Logan G.
Abstract : Leukapheresis (LA) in pediatric leukemia is performed for leukostasis, a life-threatening emergency in the setting of extremely increased blast cell counts. The authors aimed to assess the epidemiology of pediatric leukemia who received LA. The authors reviewed US nationally representative admission records of patients less than 20 years of age in the Kids' Inpatient Database for the years 2000, 2003, 2006, 2009, 2012, and 2016. Incidence of new leukemia cases who underwent LA were calculated for the years 2009, 2012, and 2016. Cox and logistic regression analyses were performed to ascertain the risk factors for adverse outcomes. There were 526 admissions for pediatric patients with acute lymphoblastic leukemia (ALL) (n=328), acute myeloid leukemia (AML) (n=124), or chronic myeloid leukemia (CML) (n=74) who underwent LA over the study period. The incidence of leukemia cases that required LA was lower in 2016 than in 2009 or 2012 (1.4%, 2.2%, and 2.7%, respectively; P =0.001). In-hospital mortality was higher in AML than ALL (hzard ratio, 3.2; 95% confidence interval, 1.1-9.1). None with CML died during admission. This first population-based study of LA in pediatric leukemia showed a decreased utilization of LA over recent years. The higher inpatient mortality in AML, as compared with ALL or CML, warrant further investigations.